Protein and lipid oxidation affect the viscoelasticity of whey protein layers at the oil–water interface. Issue 11 (14th October 2016) - Berton‐Carabin, Claire C.; Schröder, Anja; Rovalino‐Cordova, Ana; Schroën, Karin; Sagis, Leonard
Abstract : Protein and lipid oxidation are prevailing issues that negatively affect the nutritional and sensory quality of food emulsions. It is probable that such oxidative modifications affect the functional properties of proteins, and in particular their ability to form densely packed, interconnected viscoelastic films at the oil–water interface. However, these aspects have hardly been investigated. We induced controlled levels of protein and lipid oxidation using whey protein solution and sunflower oil as substrates, respectively. The adsorption kinetics, surface activity, and dilatational interfacial rheology of whey proteins at the sunflower oil–water interface were investigated using a drop tensiometer. Both protein and lipid oxidation led to a decrease in interfacial elasticity compared to the non‐oxidized samples, though through different pathways: protein oxidation led to a broad range of proteinaceous species, including peptides and aggregates, which did not form an interconnected network. Lipid oxidation induced the formation of surface active compounds, which presumably formed segregated domains at the interface. Practical applications : Oxidative reactions prevent whey proteins to form strong, viscoelastic layers at the oil–water interface. This could, in turn, drastically affect their ability to stabilize food emulsions. These findings suggest that considering the initial oxidative state of ingredients should be an integral part of food emulsion formulation. Protein oxidation leads to the formation of a broad range of proteinasceous material, including peptides and aggregates. Lipid oxidation leads to the formation of surface‐active compounds. Both oxidative reactions decrease the ability of whey proteins to form interconnected, elastic interfacial layers at the oil–water interface. Abstract : Protein oxidation leads to the formation of a broad range of proteinasceous material, including peptides and aggregates. Lipid oxidation leads to the formation of surface‐active compounds. Both oxidative reactions decrease the ability of whey proteins to form interconnected, elastic interfacial layers at the oil–water interface.